Seroprevalence of hepatitis B infection and active immunization in Ecuadorian Amazonian indigenous people: A cross-sectional study - Romero-Sandoval, Natalia; Flores, Andres; Mora-Bowen, Nicole; Arisqueta, Lino; Moreno, Cristina; Douce, Richard; Martín, Miguel (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Hepatitis B surveillance is crucial. We proposed to describe the seroprevalence of Hepatitis B infection and the associated factors among Ecuadorian Amazonia communities. Outline: A serologic cross-sectional study was carried out in subjects over two years old. We classified seropositivity according to the Centers of Diseases Control criteria and recorded sex, age, temporary migration, sometime Hepatitis B in their life, and previous vaccination. Results: Out of 215 participants, 50.0%, 8.8%, 1.9%, and 1.4% were susceptible, immune due to natural infection, chronic infection, and early acute HBV infection, respectively. Of the 8 people who reported having ever been diagnosed with Hepatitis B, none showed chronic or acute infection and one was positive for immunity due to the vaccine. HBsAg was found in 3.3% (95% IC 0.9-7.0) and was higher among those who migrate 7.7% (p-value 0.04). 16.3% (95% CI 11.6-21.4) was immune due to HBV vaccination. Among the 58 participants who declared having received the vaccine, 20.7% presented post-vaccine immunity. Implications: Participants who should have benefited from the vaccination campaign (susceptible) are those with the lowest immune response due to vaccination. To assessing the burden of viral hepatitis in people living in marginalized areas and guide preventive measures is mandatory.